Forced swim stress exacerbates inflammation-induced hyperalgesia and oxidative stress in the rat trigeminal ganglia - Ro, Jin Y.; Zhang, Youping; Asgar, Jamila; Shou, Huizhong; Chung, Man-Kyo; Melemedjian, Ohannes K.; Da Silva, Joyce T.; Chen, Shou (Frontiers in Pain Research, 2024)
This study investigates the impact of combining psychophysical stress, induced by forced swim (FSS), with masseter inflammation on reactive oxygen species (ROS) production in trigeminal ganglia (TG), TRPA1 upregulation in TG, and mechanical hyperalgesia. In a rat model, we demonstrate that FSS potentiates and prolongs CFA-induced ROS upregulation within TG. The ROS levels in CFA combined with FSS group surpass those in the CFA-only group on days 4 and 28 post-treatment. FSS also enhances TRPA1 upregulation in TG, with prolonged expression compared to CFA alone. Furthermore, CFA-induced mechanical hyperalgesia is significantly prolonged by FSS, persisting up to day 28. PCR array analyses reveal distinct alterations in oxidative stress genes under CFA and CFA combined with FSS conditions, suggesting an intricate regulation of ROS within TG. Notably, genes like Nox4, Hba1, Gpx3, and Duox1 exhibit significant changes, providing potential targets for managing oxidative stress and inflammatory pain. Western blot and immunohistochemistry confirm DUOX1 protein upregulation and localization in TG neurons, indicating a role in ROS generation under inflammatory and stress conditions. This study underscores the complex interplay between psychophysical stress, inflammation, and oxidative stress in the trigeminal system, offering insights into novel therapeutic targets for pain management.